Agrobiodivesificacion de playas y barreales y su función en la economia familiar ribereña de la Amazônia Peruana - RIOS ARÉVALO, Michelly (2005)
The present agrobiodiversidad at playas and barreales them of the Amazonian Peruvian it was studied in Muyuy, sector once three hours was located of Iquitos City, the Region Loreto capital. The objective of work was guided to measure the agrobiodiversidad in these expeditious environments and its contribution in the family riverside economy. Firstly, we see than the agricultural activity practiced at playas and barreales them it takes place through a role of production with cultivations of short vegetative period (rice, caupí, peanuts, etc.); this to decrease the risk provoked by the repiquetes or flooding new yearly cycle. Data in the crop years of 1999 and 2004, they allow identifying the establishment of 9 and 2 cultivations respectively, this variation is due to flooding different behavior; variation that at the same time the formation of different environments like playas and barreales them: heights, means, and basses. From now on, we see than optimal barreal environment for the production of rice, it was promoted with agricultural credits - 2004; this implicated logically the incursion varieties certified or overdue ( Inti, Ecoarroz, Jar, Capirona, and Amor 107 ), tender to a fast inundabilidad like the happened in the crop year 2004. The results evidence than communities SPC, ODN, TPZ, CON and DDM benefited with the credits and affected by the flooding, managed to rescue to 10 % of the production expected of rice; find farmers' cases of the communities here DDM and MAZ that used precocious varieties not promoted with credits like the Milagrito also they managed rescue of 50 to 60 % of production. The farmers that established caupí at playas managed to make good use of approximately 10 % of the hoped-for production. The flooding that affected the cultivations near to the period of harvest created propitious environments for nutrition and protection of some fishes and tortoises sorts, this at the same time increased factors or resources of use for the farmers; here, the work of fishing was executed so much for overall consumption and the commercialization for part of some cases found in the studied communities, the more representative like the family shows 11 than as from this work of fishing you got the 2,9% of recuperation on the basis of the profitable calculation from the established cultivations; and of tortoises' capture the 3,1%. It is concluded that the cultivations lost by flooding can be recovered in more significant percentages, if adequate handlings without altering the environments of production be used as it happens with the chemical application of agriculture.